STRATEGI MANAJEMEN ISU DALAM MEMPERTAHANKAN CITRA PERUSAHAAN (Studi Pada Departemen Policy, Government, and Public Affairs Rumbai PT. Chevron Pacific Indonesia) - Permana, Radittya; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Strategy in managing the issue is one of public relations duties as the company was hit by the issue . Public relations strategies used by public relations practitioners with the aim of resolving the problems being faced by an organization or company . Development of negative issues through mass media, both print and online media on the issue of Chevron bioremediation could adversely affect the company's image . Therefore, companies should have an effective management strategy to address the issue of the matter. This study aims to determine strategies PGPA Department PT . CPI in determining strategy management measures and to identify issues of planning prevention strategies through activities related to the development of communication strategies negative issues Bioremediation Chevron .The method used in this study is a qualitative method that attempts to explain the phenomena that occur in accordance with the results obtained with a set of 4 ( four ) the subject of research as an informant by purposive technique . The object of this study is the Strategy Department PGPA PT . Chevron Pacific Indonesia in management of issues for maintaining a corporate image based on the data information obtained through observation , interviews , and documentation . Technical analysis of the data in this study using a model of interactive data with data validity checking is done using the extension of participation and triangulation techniques .The results showed that the issue of management strategies performed with responsiveness . Deppartemen PGPA PT . CPI taking strategic steps to monitor the progress of society and collect data about a growing issue . PGPA Department issues management strategy performed by loading and provide information and clarification and hold issues through the mass media as the implementation of the communication strategy . Activity monitoring the performance of the implementation focused on the issue memantai potential issues by developing internal resource